Implementation of Religious Character Education at SD Muhammadiyah 1 Candi Labschool UMSIDA During the Covid 19 Pandemic - Muhlasin Amrullah; Eva Dwi Endah Silvia (Proceedings of The ICECRS, 2021)
This study aims to explain the value of religious character education, character education practices, and barriers that affect UMSIDA character education in SD Muhammadiyah 1 CandiLab School. This research is a descriptive and qualitative research. Survey data sources include the reporter, location (event), and documents. The data collection methods used in this study were (1) observation (2) detailed interviews with teachers of SD Muhammadiyah 1 Candi Lab School UMSIDA (3) data triangulation and validation of data validity using information providers. This analysis uses interactive analysis technology which consists of four parts: data collection, data simplification, data presentation, and drawing conclusions. The results of this study are as follows: (1) Muhammadiyah elementary school teachers have tried to develop a religious personality learning model, but there is still no suitable model to improve student character education. (2) SD Muhammadiyah 1 Candi Lab Religious education in schools is carried out in designing learning activities, learning, extracurricular activities and developing school culture. (3) Barriers to the implementation of religious education in SD Muhammadiyah 1 Candi arise from factors related to students and teachers or schools. Student factors include lack of awareness to participate in activities regularly and on time. In this case the teacher lacks discipline and supervision of student activities aimed at changing students' personalities, as well as the lack of subject teachers and extracurricular teachers who choose the wrong learning method.